Patient with Unicuspid Aortic Valve and Ascending Aorta Aneurysm Treated with Ozaki Procedure and Ascending Aorta Replacement - Roussakis,Antonios (2021)
Abstract Although aortic valve replacement remains the gold standard treatment for aortic valve diseases like stenosis (AS) or insufficiency, new surgical methods have been developed with a focus in the reconstruction of the aortic valve rather than replacing it. The Ozaki procedure involves a tailored replacement of each individual valvular leaflet with glutaraldehyde-treated autologous pericardium and aims to reproduce the normal anatomy of the aortic valve. Cases of patients with unicuspid aortic valve treated with the Ozaki procedure are uncommon in the litrature and become even more rare when it comes to concomitant diseases like AS and ascending aorta aneurysm. We present the case of a 21-year-old, fit and asymptomatic male, with unicuspid aortic valve with severe stenosis and ascending aorta dilatation, surgically treated with tricuspidization of the aortic valve with glutaraldehyde-treated autologous pericardium and replacement of the ascending aorta with a straight synthetic graft. Postoperative studies showed a fully functional, neo-tailored tricuspid aortic valve with trivial regurgitation. The patient had an uncomplicated recovery, stayed in the intensive care unit for 2 days and was discharged on the 7th postoperative day.